The Effect of Work Motivation and Work Discipline on Employee Satisfaction at The Main Branch Office of Medan 20000 With Loyalty as A Moderating Variable - Siswa Pratama; Nanda Tia Losi (Management Department Universitas Islam Negeri Sumatera Utara, 2022)
This study aimed to find the effect of work motivation and discipline on team member satisfaction at the main branch office of Medan Post Office 20000, with loyalty as a moderating variable. The population in this study amounted to 91 employees and samples as many as 51 UPL employees as respondents. This type of research data was quantitative data with primary data sources. The data analysis technique used multiple linear regression analysis and moderating regression. The results showed that work motivation (X1) had a positive and significant effect on employee satisfaction, while Work discipline (X2) had no significant effect on employee satisfaction. Work motivation (X1) and discipline of work (X2) positively and significantly affected employee satisfaction. Work motivation x loyalty (X1Z) had a positive and significant effect on employee satisfaction with a value of t-count 10,098 > t-table 2,009 with a positive sign and a significance level of 0.000 <0.05. Work discipline x loyalty (X2Z) had a negative and significant effect on employee satisfaction with a t-count of 5.625 > t-table 2,009 with a negative sign and a significance level of 0.000 <0.05.Keywords: Job satisfaction, loyalty, work discipline, work motivation